Disney 100 [compact disc]. - Collins, Arthur, 1864-1933; Churchill, Frank, 1901-1942; Caselotti, Adriana, 1916-1997; Edwards, Cliff, 1895-1971; Felton, Verna, 1890-1966; Dodd, Jimmie, 1910-1964; Costa, Mary; Shirley, Bill, 1921-1989; Van Dyke, Dick; Andrews, Julie; Sherman, Richard M., 1928-; Sherman, Robert B.; et al. (Walt Disney Records, 2023)
In celebration of the Disney 100th anniversary, this CD features favorites from Three Little Pigs. Snow White and the Seven Dwarfs to Coco, Encanto, and more!